2019
DOI: 10.3389/fgene.2019.00624
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Multi-Omics Data Identifies Potential Prognostic Markers of Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the most common and among the deadliest of pancreatic cancers. Its 5-year survival is only ∼8%. Pancreatic cancers are a heterogeneous group of diseases, of which PDAC is particularly aggressive. Like many other cancers, PDAC also starts as a pre-invasive precursor lesion (known as pancreatic intraepithelial neoplasia, PanIN), which offers an opportunity for both early detection and early treatment. Even advanced PDAC can benefit from prognostic biomarkers. However, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 84 publications
(89 reference statements)
8
49
0
Order By: Relevance
“…In addition, the distribution of few hypo-CpGs were comparatively even among shelfs, s-shore and CpG islands, except for higher in N-shore. Expectedly, we observed that the CpG island and its neighborhood location (shores) were predominantly hypermethylated which is similar with an early study 32,33 . The promoter regions (TSS, 1stExon and 5′UTR) had nearly twice hyper-CpGs (63.41% vs 36.59%) compared to outside of promoter regions (body and 3′UTR), similar observations were also reported by Nitish Kumar Mishra et.al 34 .…”
Section: Identi Cation Of Differentially Methylated Cpg Sites (Dmcs)supporting
confidence: 91%
“…In addition, the distribution of few hypo-CpGs were comparatively even among shelfs, s-shore and CpG islands, except for higher in N-shore. Expectedly, we observed that the CpG island and its neighborhood location (shores) were predominantly hypermethylated which is similar with an early study 32,33 . The promoter regions (TSS, 1stExon and 5′UTR) had nearly twice hyper-CpGs (63.41% vs 36.59%) compared to outside of promoter regions (body and 3′UTR), similar observations were also reported by Nitish Kumar Mishra et.al 34 .…”
Section: Identi Cation Of Differentially Methylated Cpg Sites (Dmcs)supporting
confidence: 91%
“…A system analysis based on the hypothesis of the mRNA-miRNA-lncRNA ceRNA network may lead to a molecular signature with better prognostic value in PAAD than a single gene. The multi-omics or meta-analysis has been applied to identify the biomarkers of pancreatic adenocarcinoma especially for PDAC (Chen et al, 2018a;Klett et al, 2018;Mishra et al, 2019). Mishra et al Identified survival associated genes using multiomics data from PDAC patients (Mishra et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The multi-omics or meta-analysis has been applied to identify the biomarkers of pancreatic adenocarcinoma especially for PDAC (Chen et al, 2018a;Klett et al, 2018;Mishra et al, 2019). Mishra et al Identified survival associated genes using multiomics data from PDAC patients (Mishra et al, 2019). And Klett et al identified 17 genes that were previously recognized as PDAC biomarkers (Klett et al, 2018) and several genes (B3GNT3, DMBT1, DEPDC1B) and lncRNAs (PVT1 and GATA6-AS) have FIGURE 4 | Kaplan-Meier survival curves of the training set, test set and total set.…”
Section: Discussionmentioning
confidence: 99%
“…Svenja Wiechmann 1,2,3 , Elena Saupp 4 , Daniela Schilling 4,5 , Stephanie Heinzlmeir 1 , Günter Schneider 6 , Roland M. Schmid 6 , Stephanie E. Combs 2,3,4,5 , Bernhard Kuster 1,2,3,7 , and Sophie Dobiasch 2,3,4,5,* Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive cancers and known for its extensive genetic heterogeneity, high therapeutic resistance, and strong variation in intrinsic radiosensitivity. To understand the molecular mechanisms underlying radioresistance, we screened the phenotypic response of 38 PDAC cell lines to ionizing radiation.…”
Section: Radiosensitization By Kinase Inhibition Revealed By Phosphopmentioning
confidence: 99%